A comparison of four native bluestem pastures - Smith, E.F.; Richardson, D.; Westmeyer, H.W.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
This test compares steer weight gains on four bluestem pastures to determine whether differences among the pastures might influence steer performance. Other than being in different pastures, all steers were treated and fed alike. The supplemental feed during the winter period was offered free choice and depended on either salt or urea or a combination of the two to limit consumption to under 2 pounds of supplemental feed per steer daily. Only salt was supplied during the summer.
Keywords: Beef; Bluestem pastures; Gain; Performance